Survival Strategy of Small Business in Point 11 Jakarta Selatan - Stevano Putra Hardianto; Diena M Lemy; Rudy Pramono (Institute of Computer Science (IOCS), 2022)
The Covid 19 pandemic is affecting Indonesia, like other nations around the globe. The call to stay at home to prevent the spread of the virus has an impact on economic upheaval, one of which is affected business actors. Therefore, in order to carry on conducting business in the midst of a pandemic, corporate actors will require a survival strategy. In order to escape the Covid 19 pandemic, food and beverage vendors at Point 11 Pondok Indah undertook this investigation. As a research tool, a list of questions was employed in this study to analyze qualitative descriptive data. Businesses in the Point 11 Pondok Indah region served as the research's sources. The findings of this study advise business actors to begin utilizing online marketplaces like Gofood and Grabfood to maximize sales under these circumstances. To encourage customers to buy their items, businesses must also focus on providing high-quality goods and clean environments. Business players that wish to launch a business in a setting like this must comprehend the findings of this study in order to survive and adjust to environmental conditions.